Respuesta :
Answer:
[tex]P(x)=2x^3-2x^2-49x+48[/tex]
Step-by-step explanation:
Let the original polynomial be [tex]P(x)[/tex].
We know that when it is divided by [tex](x-5)[/tex], the quotient is [tex]2x^2+8x-9[/tex] and we get a remainder of 3.
Therefore, this means that:
[tex]\frac{P(x)}{x-5}=2x^2+8x-9+\frac{3}{x-5}[/tex]
Remember what it means when we have a remainder. Say we have 13 divided by 3. Our quotient will be 4 R1, or 4 1 over 3. We put the remainder over the divisor. This is the same thing for polynomials.
So, to find our original polynomial, multiply both sides by [tex](x-5)[/tex]:
[tex](x-5)\frac{P(x)}{x-5}=(x-5)(2x^2+8x-9+\frac{3}{x-5})[/tex]
The left side will cancel. Distribute the right:
[tex]P(x)=2x^2(x-5)+8x(x-5)-9(x-5)+\frac{3}{(x-5)}(x-5)[/tex]
Distribute:
[tex]P(x)=(2x^3-10x^2)+(8x^2-40x)+(-9x+45)+(3)[/tex]
Combine like terms:
[tex]P(x)=(2x^3)+(-10x^2+8x^2)+(-40x-9x)+(45+3)[/tex]
Evaluate:
[tex]P(x)=2x^3-2x^2-49x+48[/tex]
And we're done!
Answer: 2x^3 - 2x^2 - 49x + 48
Explanation:
Let a be the original polynomial
Where a/(x-5) = 2x^2 + 8x - 9 (remainder 3)
a = (2x^2 + 8x - 9)(x-5) + 3
a = 2x^3 - 10x^2 + 8x^2 - 40x - 9x + 45+3
a = 2x^3 - 2x^2 - 49x + 48
Explanation:
Let a be the original polynomial
Where a/(x-5) = 2x^2 + 8x - 9 (remainder 3)
a = (2x^2 + 8x - 9)(x-5) + 3
a = 2x^3 - 10x^2 + 8x^2 - 40x - 9x + 45+3
a = 2x^3 - 2x^2 - 49x + 48